Aplikasi Pemetaan Jalur Rekreasi dan Olahraga Berbasis Web (Studi Kasus di Kabupaten Badung) - Adi Rahmadi (LPPM Universitas Dhyana Pura, 2015)
Cycling and enjoying the beautiful scenery in Badung regency is one of the most fun activity or useful activities therefore by using advanced technology of information and internet we created a web based bicycle pathways mapping, equipped with the suitable type of bicycle which could help the society and government to locate the existing tourism spot and bicycle pathways.In the making of the information system, the planning and design concept are done withthe data collecting, making DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), the database using PHP and MySQL, and implementing those further.The results of this application would be very helpful for the society, especially for the bike community and the Badung regency tourism board to give the information about the tourism spot and the identify the bicycle pathways which is located in the Badung regency.Keywords : Badung, bicycle pathways, mapping, PHP, MySQL